유통과학연구의 현재와 미래 - 김동호; 윤명길 (Journal of distribution science, 2012)
2014년도 12월말부터 시행하는 한국연구재단의 등재지 제도의 폐지는 한국 내에 존재하는 연구논문집 향방에 커다란 지각변동의 요인으로 작용할 것으로 예상되고 있다. 이러한 상황은 한국유통과학회에서 발행하는 유통과학연구를 비롯한 3개의 연구논문집에게는 커다란 기회로 작용할 것이며, 이번 기회를 잘 활용한다면 조속한 성장과 발전을 도모할 수 있을 것이다. 한국유통과학회에서 발행하는 유통과학연구는 1999년을 시작으로 꾸준한 발전을 유지하여 왔고, 초창기 연 2회 발행하던 체제를 개편하여, 연 4회를 발행 하다가, 2012년에는 연 12회 발행하는 사회과학분야에서 가장 선두로 나가는 연구논문집으로 성장했다. 2011년 7월에는 전면 영문으로 홈페이지를 개편하여, 지속적으로 게재논문을 무료로 열람토록 하였고, 그 결과 2012년 들어서서 해외에서 접속하여 유통과학연구 홈페이지를 열람하는 이용자의 숫자가 급속히 증가하였다. 더욱이 최근 들어서서는 해외석학들의 논문 투고가 꾸준한 증가 추세에 있다. 예를 들어서, 2012년 3월에는 종전과 달리 해외석학들의 투고논문이 4편에 이를 정도로 학회의 지명도가 높아지고 있다. 이러한 상황은 본 유통과학연구가 한국 내에서의 지명도보다 외국에서의 지명도가 높아지고 있다는 점을 의미하는 것이다. 그러나 현시점에서 반추할 때, 이러한 발전은 현재로서는 긍정적인 요인으로 작용될 수는 있으나, 학회운영 및 연구논문집의 지속적인 상태점검과 특성에 맞는 전략도출 및 실행이 없는 한 미래의 경쟁력을 기약할 수 없는 불투명한 환경에 처해 있다는 점을 인지해야 한다. 따라서 본 연구의 목적은 한국유통과학회에서 발행하는 유통과학연구가 국내외 위상을 높이고 해외에서 유명저널이 되기 위해서는 당면과제와 문제점을 찾아내고 효율적이고 실용적인 여러가지 해결 대안을 모색 제시하고자 함에 있다. 즉, 본 연구는 한국유통과학회의 연구논문집인 유통과학연구의 과거, 현재, 그리고 미래에 대하여 논하고, 학회운영과 관련하여 편집관리 및 시스템운영을 전반적으로 점검하여 문제점과 해결점을 모색하고 제시하였다. The recent announcement of the National Research Foundation of Korea (NRF) to cease journal accreditation operations as of the end of the year 2014 can easily influence the future of many research journals in Korea. Although this plan has not yet been formalized or structured, its facilitation would be the major turning point for the current Korean research and scholarly journals and publications. In addition, the NRF’s plan to select and fund top 20 or more research journals over the five year period beginning 2015 suggests that the competition will most likely increase among Korean journals. Each journal would need to develop its unique strategy to improve and strengthen its competitiveness to become or maintain its position as a major research journal in Korea. The Korean Distribution Science Association (KODISA) and its research journal, Journal of Distribution Science (JDS), has been continuously improving its reputation as a reputable journal in the distribution and related fields since its establishment in 1999. Due to demand, JDS has had to undergo several changes in its publication cycle first from semiannual publication to quarterly, then finally to monthly publications in 2012, and has become one of the major social science journals in Korea. Furthermore, with the redesigning of its webpage with English language in July of 2011, KODISA has made the published journals freely accessible and available to both domestic and foreign researchers, scholars, practitioners, and learners. These changes have resulted in the rapid increase in the bounce rate and the number of journal submissions by foreign scholars, with four research articles having been submitted by foreign scholars just in March of 2012 alone. However, although the changes and outcomes have resulted in a reasonable success so far, the achievement may only become a short-term success without continuously developing, improving, and implementing both effective and efficient strategies through critical, thorough, and frequent examinations and evaluations of both KODISA and JDS. As such, the purpose of this research is to carefully examine both KODISA and JDS to identify problematic factors and to develop appropriate strategies to change or modify those problems for further strengthening and improving their reputation and status. The paper examines and analyzes the past, present, and future of KODISA and JDS and their managerial, operational, and systematic procedures and operations. The narrow scope of research and inefficiencies in promoting the association and the journal and the improvement of impact factors are identified as the notable problems that could hinder JDS from being included in SCOPUS or SSCI in the near future. This type of examination and exploration has not been previously conducted, so the major limitation of this paper can be identified as not meticulously elaborating on the problems nor proving detailed recommendations based on the existing researches. This article asserted that solving the problem of the narrow scope of research would lead to facilitation of resolving other inefficient problems. Inclusion of international academic disciplines to the distribution and their related fields would be the viable initiation of expanding the research area, and this strategy could promote the journal as well as improve its impact factors. The narrow scope of research seems to be a good research topic and merit further exploration as an individual research project, because this kind of research could yield the creation of new understandings or theories. KCI Citation Count: 10